Investigating parents' degrees of trust and communication towards teachers in Indonesian kindergartens - Elly Ramadhani Sipayung; Ching Ching Cheng (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The parent-teacher interaction has been identified as a critical component in the development of children. Teachers' capacity to educate children is influenced by the level of trust parents have in them. Creating a supportive environment at home and cooperating with the school are essential components of a positive educational experience for all parties involved. Prior research, however, found little parental involvement particularly in establishing a quality relationship with the schools in Indonesian kindergartens. This research aimed to examine Indonesian parents’ degrees of trust and communication toward the teachers in 8 kindergartens in Dairi regency, North Sumatra. In constructing the questionnaire, 9 early childhood education practitioners were invited to make content suggestions before conducting a validity test and reliability through factor analysis. The validity is guaranteed by the Kaiser-Meyer-Olkin Measure result of .872 and Barlett's Test (Chi-Square = 3451.561, df = 406, p 0.05). The reliability was measured using Cronbach's Alpha obtaining an alpha coefficient of .870, indicating good reliability. The findings from the 203 questionnaires consisting of 29 items that were distributed indicate parents’ favorable attitudes toward teachers. Besides, the parent’s background does not reflect their attitudes and practices. Suggestions, including delivering the concept of partnership to the parents and increasing the opportunities of participating in school activities, are provided to promote greater quality of the parent-teacher relationship.